Counselling your staff - Redman, Warren (New Delhi : Kogan Page, 1996)
Provides the busy manager with an explanation of the skills involved in the staff counselling process. The text features examples and illustrations of counselling issues, and addresses common questions asked by new managers.
Keywords: Employees -- Counseling of